Nilavembu Kudineer (Siddha Polyherbal Decoction) for the Management of COVID-19 – Evidences from Clinical and In-silico Studies: Nilavembu Kudineer for COVID-19 - Pakkir Maideen, Naina Mohamed (Indian Journal of Integrative Medicine, 2022)
Background and Aim: The current pandemic of coronavirus Disease 2019 (COVID-19) is caused by novel coronavirus or severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), and it is managed mainly by using repurposed antiviral drugs along with symptomatic treatment and supportive care. This review focuses on the use of Nilavembu Kudineer in asymptomatic or mildly symptomatic COVID-19 patients. Methods: The literature was searched in databases such as Medline, PubMed Central, PubMed, Google Scholar, Science Direct, bioRxiv, medRxiv, Research Square, EBSCO, Scopus, Web of Science, EMBASE, Directory of Open Access Journals (DOAJ), and reference lists to identify articles relevant to the clinical and in silico studies evaluating the efficacy of Nilavembu Kudineer in the management of COVID-19. Results: Many clinical studies revealed that Nilavembu Kudineer might be effective in the management of asymptomatic or mild-symptomatic COVID-19 patients along with standard care. Similarly, many molecular docking studies have been performed to determine the inhibitory potential of phytoconstituents of Nilavembu Kudineer against SARS-CoV-2. Conclusion: More randomized, controlled trials would further establish the safety and efficacy of Nilavembu Kudineer in COVID-19 patients.